Glucose-induced monoubiquitination of the Saccharomyces cerevisiae galactose transporter is sufficient to signal its internalization - Horak, J; Wolf, D H (Journal of bacteriology, 2001)
In Saccharomyces cerevisiae, the addition of glucose to cells growing on galactose induces internalization of the galactose transporter Gal2p and its subsequent proteolysis in the vacuole. Here we report that the essential step in Gal2p down-regulation is its ubiquitination through the Ubc1p-Ubc4p-Ubc5p triad of ubiquitin-conjugating enzymes and Npi1/Rsp5p ubiquitin-protein ligase. Moreover, Gal2p appears to be stabilized in mutant cells defective in the ubiquitin-hydrolase Npi2p/Doa4p, and the mutant phenotype can be reversed by overexpression of ubiquitin. An analysis of the fate of Gal2p in cells overexpressing wild-type ubiquitin as well as its variants incompetent to form polyubiquitin chains showed that monoubiquitination of Gal2p is sufficient to signal internalization of the protein into the endocytic pathway.
Keywords: ubikvitiny; Saccharomyces cerevisiae Proteins; regulace genové exprese u hub; Glucose; Ubiquitins; proteiny přenášející monosacharidy; endozomální třídící komplexy pro transport; Saccharomyces cerevisiae; ligasy; Ligases; Ubiquitin-Protein Ligases; glukosa; ubikvitinligasy; Ubiquitin-Protein Ligase Complexes; komplexy ubikvitinligas; Endosomal Sorting Complexes Required for Transport; Gene Expression Regulation, Fungal; Saccharomyces cerevisiae - proteiny; Monosaccharide Transport Proteins